2009
DOI: 10.2131/jts.34.s31
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative work on evaluation of ovarian toxicity 2) Two- or four-week repeated dose studies and fertility study of mifepristone in female rats

Abstract: -In order to assess ovarian pathological changes and their relationship to changes in female fertility parameters, mifepristone, a progesterone receptor antagonist, was selected as the test article and was administered orally to female rats at dose levels of 0, 0.8, 4, 20 and 100 mg/kg for 2 or 4 weeks in repeated dose-toxicity studies and in a female fertility study at dose levels of 0, 0.8, 4 and 20 mg/kg from > 2 weeks before copulation to postcoital day 7. In the repeated dose toxicity studies, persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…The effects of tamoxifen and RU486 on females are dose-dependent, with higher doses inflicting more disruption to oestrous cycles and body condition [38,39,71,73,59,74]. Our lower doses of tamoxifen and RU486 produced the disruption of oestrous cycles without complete abolishment of cycling, moderation of fat stores as seen by tail width modifications, and some body mass changes, similar to the effects of these doses on other species [39,38,72,73,59,74].…”
Section: Body Condition and Reproductive Indicesmentioning
confidence: 54%
“…The effects of tamoxifen and RU486 on females are dose-dependent, with higher doses inflicting more disruption to oestrous cycles and body condition [38,39,71,73,59,74]. Our lower doses of tamoxifen and RU486 produced the disruption of oestrous cycles without complete abolishment of cycling, moderation of fat stores as seen by tail width modifications, and some body mass changes, similar to the effects of these doses on other species [39,38,72,73,59,74].…”
Section: Body Condition and Reproductive Indicesmentioning
confidence: 54%
“…Dose volumes for both agents were 5 mL/kg, according to twoor four-week repeated dose studies of IM (Tsubota et al, 2009) and RU (Tamura et al, 2009).…”
Section: Test Agents and Dosingmentioning
confidence: 99%
“…The study design and number of animals used in the experiment 1 are shown in Table 1. Dose levels, 4 mg/kg for IM and 100 mg/kg for RU, at which UFs were induced by multiple-dose, were selected (Tsubota et al, 2009;Tamura et al, 2009). The ovaries, uteri, and vaginas were removed, fixed in 10% neutral buffered formalin, embedded in paraffin, sectioned at 4 μm, and stained with hematoxylin and eosin (HE).…”
Section: Experiments 1 (Histopathology)mentioning
confidence: 99%
See 2 more Smart Citations